2013
DOI: 10.1177/0022487113488945
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preservice Preparation and Early Career Support on Novice Teachers’ Career Intentions and Decisions

Abstract: A rationale for providing high-quality support during teachers’ early years is to develop further the skills teachers acquire during preparation and to help overcome weaknesses that might lead them to abandon the profession. Yet, almost no consideration has been given to potential interactions between preservice preparation and induction support received. This study utilizes survey and administrative data to examine the effects, including interactions, of preservice preparation and early career support on new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 44 publications
4
75
0
2
Order By: Relevance
“…Turnover intentions originate, intensify or fade away in the learning processes in teacher education and in work at school (Hong, 2010). It has been suggested that although teachers' turnover intentions do not always lead to a decision to leave the profession, nonetheless they may affect teachers' efforts and effectiveness (DeAngelis, Wall, & Che, 2013;Ladd, 2011). Teacher-student interaction constitutes a new context for early career teachers' learning that may challenge the development of their sense of professional agency and even lead to turnover (McCormack, Gore, & Thomas, 2006).…”
Section: Early Career Teachers' Turnover Intentions and Perceived Inamentioning
confidence: 99%
“…Turnover intentions originate, intensify or fade away in the learning processes in teacher education and in work at school (Hong, 2010). It has been suggested that although teachers' turnover intentions do not always lead to a decision to leave the profession, nonetheless they may affect teachers' efforts and effectiveness (DeAngelis, Wall, & Che, 2013;Ladd, 2011). Teacher-student interaction constitutes a new context for early career teachers' learning that may challenge the development of their sense of professional agency and even lead to turnover (McCormack, Gore, & Thomas, 2006).…”
Section: Early Career Teachers' Turnover Intentions and Perceived Inamentioning
confidence: 99%
“…D'abord, une pénurie d' enseignants qualifiés dans plusieurs champs et dans plusieurs ordres d' enseignement s' engage graduellement au Québec (Tardif, 2016) et coïncide avec le taux à la hausse du décrochage des débutants, comme dans d'autres pays nord-américains, depuis les dernières années (Bélair et Lebel, 2007;Bourque et al, 2007;Ingersoll et Strong, 2011;Karsenti et al, 2013;Smith et Ingersoll, 2004). Ce décrochage des enseignants affecte la qualité de l' enseignement offert aux élèves et, par le fait même, leur apprentissage, en entrainant une certaine discontinuité dans l'enseignement (DeAngelis, Wall et Che, 2013;Hattie, 2009;Leroux et Mukamurera, 2013;Synar et Maiden, 2012). Le décrochage peut également nuire à l' établissement d'une forte cohésion au sein de l' équipe-école qui est pourtant déterminante dans l' établissement d'un climat favorable à la persévérance scolaire (Karsenti et al, 2013).…”
Section: Le Décrochage Des Enseignants Débutantsunclassified
“…Finally, we also know from research that ongoing professional support of teachers, whether they have been certified through traditional or alternative programs and especially during the early years of their careers, is critical in reducing the number who leave the profession (e.g., DeAngelis, Wall, & Che, 2013). Thus, a related issue of concern is the extent to which the charter school and alternative certification track movements will lead to an even more unbalanced emphasis on teacher production, in contrast to teacher support.…”
Section: The Perpetuation Of Free Market Ideology: the Increase In Almentioning
confidence: 99%